Assistance or Resistance? Evaluating the Intersection of Automated Journalism and Journalistic Role Conceptions - Schapals, Aljosha Karim (2020)
Newsrooms are a social context in which numerous relationships exist and influence news work—be it with other journalists, the audience, and technology. As some of these relations change due to technological innovations, new hybrid contexts—technologies that are interwoven with newsroom values, routines, and socio-cultural experiences—can emerge. One key question is how journalists conceptualise and interact with such technologies, and to what degree they retain (creative) agency in the process. Therefore, this study evaluates the intersection of automated journalism and journalistic role conceptions. Using Hanitzsch’s and Vos’s circular model of journalistic roles (2017) and Deuze’s understanding of journalism as an ideology (2005) as a theoretical framework, this study examines some of the discursive aspects of automated journalism by asking: To what extent are journalistic roles (a) challenged or (b) advanced as a result of automated journalism? Our findings more closely align with the latter, pointing to a strong sense of discursive maintenance of journalists’ roles and their core skillset and thus suggesting a high degree of ideological continuity in the face of industrial disruption. It concludes with an agenda for future research and stresses that at times when journalism and automation intersect, the field would benefit from incorporating emerging conceptual frameworks such as human–machine communication.